Mission and church in Malawi : the history of the Nkhoma Synod of the Church of Central Africa, Presbyterian, 1889-1962 - Pauw, Christoff Martin (Stellenbosch : Stellenbosch University, 2012)
Thesis (DTh)--Stellenbosch University, 1980.